The electrochemical oxidation of cobalt tris(dithiocarbamates) and tris(diselenocarbamates) in acetonitrile; a combined spectroscopic and voltammetric study - Alden, J; Bond, A; Colton, R; Compton, R; Eklund, J; Mah, Y; Mahon, P; Tedesco, V (1998)
The electrochemical oxidation of cobalt(III) dithiocarbamates and diselenocarbamates (CoL3) in acetonitrile + 0.1 M Bu4NPF6 is shown to occur via the mechanism: (E) CoL3↔[CoL3]+ + e-; (C2) 2[CoL3]+ → [Co2L5]+ + oxidized ligand; (C) [Co2L5]+ + 2CH3CN → CoL3 + [CoL2(CH3CN)2]+. A combination of electrochemical, electrospray mass spectrometry, and 59Co/77Se NMR experiments confirms that the binuclear species, [Co2L5]+, reacts with acetonitrile forming CoL3 and [CoL2(CH3CN)2]+. At the electrode surface, CoL3 species generated by this reaction may then be reoxidised resulting in an enhanced peak or limiting current. Consequently, the oxidation of CoL3 in acetonitrile represents an overall EC2C mechanism. The data obtained from cyclic voltammetry at Pt disc electrodes and steady-state hydrodynamic voltammetry at platinum channel electrodes for oxidation of CoL3 were modelled according to this EC2C scheme using the commercial DigiSim electrochemical simulation package and the backwards implicit finite difference technique, respectively. Good fits between experiment and simulation were obtained using the same kinetic parameters for both methods. The calculated dimerisation rate constant (C2 step) is similar to the value obtained in dichloromethane, which is uncomplicated by reaction of [Co2L5]+ with the solvent. It was observed that if either voltammetric technique was used in isolation, a wider range of combinations of kinetic parameters could be utilised in order to obtain satisfactory fits between experiment and theory. © 1998 Elsevier Science S.A. All rights reserved.